Appeals to shared suffering in the context of the Israeli-Palestinian conflict - Lukas Reinhardt; Harvey Whitehouse (PLoS ONE, 2025)
Shared suffering can bond groups together and motivate fighting and even dying for the group leading to vicious cycles of violence while the suffering of the outgroup is routinely overlooked. But could the power of shared suffering also be harnessed to reduce tensions? Here we present evidence that a speech appealing to suffering shared by both sides in the Israeli-Palestinian conflict delivered by a professional politician in December 2023 can foster identity fusion, trust and openness to friendship towards the outgroup – Palestinians or Israelis – in a sample of Muslim and Jewish Americans (n = 159). Effects partially persisted three days after exposure to the speech. In a follow-up study we found that the same speech also increased positive attitudes towards Israelis and Palestinians in a sample of the general US population (n = 361).